Study Of Application Of Design Thinking In Entrepreneurial Skill Development For Start Ups - Dr. Jayasree Nambiar (Journal of Advanced Zoology, 2024)
I Design thinking is a human-caused approach to sort out problems and prepare the mindset to deal with the challenges in business. This is a step-by-step method to deal with the entire aspects of production right from product decision to launch of the product. The proper method to know the consumer’s need and formulation of suitable action plan to devise solutions is required before product decision. The constructive interaction between design thinking and entrepreneurship development is well-known. Reliable solutions can be derived through design thinking in developing ideas for start-up ventures. The upcoming entrepreneurs can explore many open-ended options and design the options to capture the market share.